HAK KONSTITUSIONAL PEREMPUAN DALAM KEBIJAKAN PERLINDUNGAN TERHADAP KEKERASAN BERBASIS GENDER (KGB) - Putri, Rezi Tri; Susmita, Susmita; Aripin, Rahmat; Robensyah, Andes; Wardani, Khofifah Kusuma; Putri, Filqi Abdillah; Ramadani, Ramadani (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
In Indonesia, although policies such as Law No. 23 of 2004 on the Elimination of Domestic Violence and Law No. 12 of 2022 on Sexual Violence Crimes have been enacted, their implementation and enforcement face numerous challenges, including social stigma, weak law enforcement, and limited support facilities. These issues are exacerbated by a patriarchal culture that often views violence as a private matter, making it difficult to address through the legal system. As a state that guarantees human rights under Articles 28A–28I of the 1945 Constitution, Indonesia has a constitutional obligation to protect women from all forms of violence. However, this effort is hindered by weak inter-agency coordination, low public awareness, and limited infrastructure to support victims' recovery. This study aims to analyze the extent to which women’s constitutional rights are protected in policies addressing GBV in Indonesia. The research examines the harmonization of national policies with international instruments such as CEDAW, evaluates the capacity of law enforcement, and analyzes victims’ access to protection services. The findings are expected to provide strategic recommendations, including strengthening policies through harmonization with international standards, enhancing the capacity of law enforcement agencies, and expanding access to services for victims in remote areas.